SAE Technical Paper Series 1998
DOI: 10.4271/982529
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Wood Flash-Pyrolysis Oil in Diesel Engines

Abstract: The paper describes an experimental study concerning the feasibility of using bio-oil obtained from flash pyrolysis of wood for fuelling diesel power plants. The research is based on various tests aimed at verifying relevant operative characteristics of the fuel: spray analyses, engine tests, thermogravimetric analyses (TGA), single-drop reactor tests and corrosion tests. The spray analyses show that the achievement of a satisfactory atomisation with flash-pyrolysis oil is problematic. The engine experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…At full load, combustion duration of the 30% DSPO blend operation was almost 12% lower than for FD. In the case of engine testing with other types of pyrolysis oils [40,41], long ignition delays and short combustion periods were also reported. Higher cylinder pressure and high heat release rates of pyrolysis oil combustion are also reported in the literature [42][43][44].…”
Section: Combustion Characteristicsmentioning
confidence: 96%
“…At full load, combustion duration of the 30% DSPO blend operation was almost 12% lower than for FD. In the case of engine testing with other types of pyrolysis oils [40,41], long ignition delays and short combustion periods were also reported. Higher cylinder pressure and high heat release rates of pyrolysis oil combustion are also reported in the literature [42][43][44].…”
Section: Combustion Characteristicsmentioning
confidence: 96%
“…Performance and combustion characteristics of diesel with tire pyrolysis oil (TPO) were carried out for different blending ratios and concluded that thermal efficiency was increased with the increasing of blending concentration higher than diesel. However, NOx, HC, and CO concentrations were more in emissions because of ignition delay and aromatic contents . Distilled TPO (DTPO) with diesel reduced the amount of NOx (about 8%) compared with diesel (about 10%), and HC was decreased up to 2% with virgin DTPO operations.…”
Section: Utilization Of Waste Plastic Oil With Diesel Enginementioning
confidence: 99%
“…This resulted in the worsen THC emission and there was no smoke data. The SMD (Sauter mean diameter) of the raw bio-oil was greater than the diesel fuel [35]. The SMD observed became higher with the increase of the kinematic viscosity [36].…”
Section: Smoke Emissionmentioning
confidence: 99%